THE EFFECTIVENESS OF POLICIES ON VILLAGE FUND, SOCIAL ASSISTANCE AND CAPITAL EXPENDITURE ON POVERTY ALLEVIATION IN ACEH PROVINCE - Novila Dira; Ichsan Ichsan (LPPM Universitas Malikussaleh, 2025)
Village funds, social assistance funds, and capital expenditure are important instruments in regional development that play a role in poverty alleviation efforts. This study aims to analyze the effects of village funds, social assistance funds, and capital expenditure on the poverty rate in Aceh Province. The data used in this study are panel data covering the period from 2017 to 2024. The data were obtained from the Central Bureau of Statistics (BPS) of Aceh Province and the Directorate General of Fiscal Balance (DJPK) of the Indonesian Ministry of Finance. The analytical method employed is panel data regression, with the Random Effects Model (REM) selected as the most appropriate model. The results show that village funds have a negative and significant effect on the poverty rate in Aceh Province. Social assistance funds also have a negative and significant effect on the poverty rate. Meanwhile, capital expenditure has a positive and significant effect on the poverty rate in Aceh Province. Based on these findings, it is recommended that provincial and district/city governments in Aceh manage village funds, social assistance funds, and capital expenditure more effectively to reduce poverty in the region.